Mössbauer and Electrochemical Investigations of Carbon-Rich Fe1-xCx Films. (10th July 2015) - Zhao, Xiuyun; Sanderson, R.J.; MacEachern, L.; Dunlap, R.A.; Obrovac, M.N.
Abstract: A thin film binary library of carbon-rich Fe1-x Cx (0.47 ≤ x ≤ 0.97) alloys was prepared by combinatorial sputtering of carbon and iron. The sputtered library was characterized by X-ray diffraction and room temperature 57 Fe Mössbauer effect spectroscopy to determine its microstructure. X-ray diffraction results show that the Fe1-x Cx film is amorphous in the whole composition range of the library. For 0.52 ≤ x ≤ 0.59, a hyperfine field distribution and a quadrupole splitting distribution as obtained from Mössbauer spectra indicate the presence of a ferromagnetic phase and a paramagnetic phase in this regime. With increasing of carbon content, for 0.61 ≤ x ≤ 0.97, the sextet disappears and two paramagnetic doublets splitting appear suggesting two different Fe sites. The electrochemical performance of the Fe1-x Cx film was investigated in lithium cells and the presence of Fe was found to increase the reversible capacity per mass of carbon over that of a pure carbon electrode.